FOOD ALLERGY IN INFANTS - I.I. Balabolkin ("Paediatrician" Publishers LLC, 2006)
The article deals with the etiology, growth mechanisms, clinical implications, diagnostics and treatment of the infant food allergy. The author highlights the status of the allergy to the proteins of cow milk within this age group of children. Alongside the article describes the modern approaches to the diet therapy of the infants with the allergy to the proteins of cow milk.Key words: infant, food allergy, allergy to the proteins of cow milk, diet therapy.